From the Scholarly Edition to Visualization: Re-using Encoded Data for Historical Research. - Rehbein, Malte (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2014)
This paper reports from the perspective of a historian who is investigating an early medieval manuscript, aiming at opening it up for further research and exploring its location in space, time, and intellectual context. The manuscript in question and the texts it carries show a complex, interwoven network of intra- and intertextual relations and the paper argues that only a combination, provided by computational means as the methodological key, of two usually distinct research approaches, namely close reading and distant reading, can deliver answers to the research questions imposed. The paper introduces some central methods of an interdisciplinary field, commonly known as digital humanities, in the realm of data representation (data modeling and text encoding) as well as core applications in the realm of data presentation and analysis (digital editing and visualization). As these supportive methods are neither the starting-point for historical research nor an end-in-itself, they are mirrored against scholarly practices of both, of the early Middle Ages and of modern scholarship.